Characterisation of cold plasma treated beef and dairy lipids using spectroscopic and chromatographic methods. (15th November 2017) - Sarangapani, Chaitanya; Ryan Keogh, David; Dunne, Julie; Bourke, Paula; Cullen, P.J.
Highlights: This study evaluated cold-plasma-induced lipid oxidation of model matrices, namely dairy and meat fats. The oxidation of lipids by cold plasma followed the Criegee mechanism. Oxidation products and pathways were determined using FTIR, NMR and GC–MS. A detailed mechanism of formation of oxidation products has been proposed. Abstract: The efficacy of cold plasma for inactivation of food-borne pathogens in foods is established. However, insights on cold plasma-food interactions in terms of quality effects, particularly for oils and fats, are sparse. This study evaluated plasma-induced lipid oxidation of model matrices, namely dairy and meat fats. Product characterisation was performed using FTIR, 1 H NMR and chromatographic techniques. The oxidation of lipids by cold plasma followed the Criegee mechanism and typical oxidation products identified included ozonides, aldehydes (hexanal, pentenal, nonanal and nonenal) and carboxylic acids (9-oxononanoic acid, octanoic acid, nonanoic acid), along with hydroperoxides (9- and 13-hydroperoxy-octadecadienoylglycerol species). However, these oxidation products were only identified following extended treatment times of 30 min and were also a function of applied voltage level. Understanding cold plasma interactions with food lipids and the critical parameters governing lipid oxidation is required prior to the industrial adoption of this technology for food products with high fat contents.